Uso de Lidocaína e Bupivacaína na anestesia espinhal em Trachemys dorbignyi (Duméril & Bibron, 1835) (Testudines-Emydidae) - Andrade, Mariana Batista (2010)
We aimed to investigate the efficacy of lidocaine and bupivacaine via spinal injection in promoting sensory and motor block in the regions of the tail/cloaca and pelvic members of Trachemys dorbignyi. Ten females with average weight of 1.375 kilograms (kg) were submitted to two anesthetic protocols, with an interval of 10 days: 4.6 milligrams (mg)/kg of lidocaine 2% and 1.15 mg/kg of bupivacaine 0, 5%, deposited via spinal in the coccyx region. The animals were evaluated for latent period, reasonable period and recovery period of anesthesia. For the period of latency of the tail (Lca), we obtained an average of 28.80 ± 2.29 seconds (sec) and 56.80 ± 4.78 sec for lidocaine and bupivacaine. Since the average latency of pelvic limb was 448.00 ± 48.51 sec and 487.70 ± 30.25 sec for both anesthetics. The reasonable period of anesthesia was 79.29 ± 33.11 minutes (min) for lidocaine and 116.55 ± 41.03 min in the tail/cloaca for bupivacaine. Averages corresponding to 112.03 ± 45.12 min and 150.87 ± 53.36 min were obtained in the pelvic members through use of anesthetics in the same sequence. Finally, the recovery period was 76.30 ± 32.18 min and 68.00 ± 43.35 min for lidocaine and bupivacaine, respectively. The heart rate remained within the range considered normal for reptiles. It was concluded that the use of lidocaine 2% and 0.5% bupivacaine via spinal injection is safe and effective in promoting anesthesia in the tail/cloaca and pelvic members in Trachemys dorbignyi. The duration of anesthetic effect in the tail/cloaca was significantly higher by using bupivacaine 0.5%. The times of reasonable periods of anesthesia achieved with the use of both anesthetic protocols are sufficient to perform simple and routine surgical procedures, such as amputation of the penis and suturing of skin lacerations.